Investigation of a 25 kV–50 Hz Railway-Substation Power Supply Based on a Back-to-Back Modular Multilevel Converter Topology - Kevin Tournoux; Azeddine Houari; Mohamed Fouad Benkhoris; Franck Terrien; Pierre-Louis Garmier (Energies, 2024)
This paper presents a preliminary study of a 25 kV–50 Hz railway substation power supply system. The control of a back-to-back converter based on modular multilevel converter (MMC) technology was investigated to fit with the power quality requirements of the application. One of the main challenges is the presence of constraining load conditions, under which the train circulation variability, low-frequency harmonics and critical power transients can notably decrease the power quality and lead to instability. In order to address this, cascaded controllers based on resonant controllers are proposed to ensure the desired performance. Furthermore, balancing voltage algorithms are added to avoid stress phenomena and additional losses in the studied power conversion interface. The paper presents the design of the control stages and demonstrates the robust performance of the system using a realistic loading condition of a railway substation.